2021
DOI: 10.1016/j.cocis.2021.101469
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the-art colloidal particles and unique interfaces-based SARS-CoV-2 detection methods and COVID-19 diagnosis

Abstract: In March 2020, SARS-CoV-2 based infections were declared ‘COVID-19 pandemic’ by the World Health Organization (WHO). Pandemic raised the necessity to design and develop genuine and sensitive tests for precise specific SARS-CoV-2 infections detection. Nanotechnological methods offer new ways to fight COVID-19. Nanomaterials are ideal for unique sensor platforms due to their easy manufacturing, chemically versatile properties. In this context, selected examples for integrating nanomaterials and distinct biosenso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 91 publications
0
11
0
Order By: Relevance
“…They also reported that the major hematological indicators in COVID-19 include the absolute and relative (ratios) counts of the circulating neutrophils and lymphocytes in the blood [ 9 ]. Several studies also reported clinical incidences of lymphopenia in progressing and more severe cases of COVID-19 infections in patient populations [ 10 ]. Of the numerous biomarkers in the progression of COVID-19 infection, the most conspicuous ones include creatine kinase, D-dimer, and troponin.…”
Section: Diagnosis Of Sars-cov-2mentioning
confidence: 99%
“…They also reported that the major hematological indicators in COVID-19 include the absolute and relative (ratios) counts of the circulating neutrophils and lymphocytes in the blood [ 9 ]. Several studies also reported clinical incidences of lymphopenia in progressing and more severe cases of COVID-19 infections in patient populations [ 10 ]. Of the numerous biomarkers in the progression of COVID-19 infection, the most conspicuous ones include creatine kinase, D-dimer, and troponin.…”
Section: Diagnosis Of Sars-cov-2mentioning
confidence: 99%
“…SPEs were customized in various configurations for SARS-CoV-2 detection (some components of the virus itself) [ 248 , 265 , 266 , 267 , 268 , 269 ], but also for the detection of some biomarkers useful for Covid 19 diagnosis (C-reactive protein, interleukins, tumor necrosis factor alpha, interferons, glutamate, breath pH, lymphocytes, platelets, neutrophils and D-dimer) [ 270 ]. Nanomaterials such as AuNPs, calixarene functionalized graphene, Au@Fe 3 O 4 nanocomposite (400 nm) and carbon black served as catalysts, bioreceptor or labels, but, also, they improved the electrochemical performance of the SPE-based sensors applied for the virus detection [ 248 , 265 , 266 , 267 , 268 , 269 ]. In the case of biomarkers sensing, several nanomaterials have been employed for SPEs modification, such as rGO, AuNPs and Ag/Pt-graphene nanocomposite [ 270 ].…”
Section: Metal Nanoparticles and Carbon-based Nanomaterials In (Bio)sensors Designmentioning
confidence: 99%
“…Shetti et al described conventional and nanotechnology-based sensors for COVID-19 [ 77 ]. Recent efforts in the applications of colloidal particles and nanoparticles for the diagnostics and treatment of COVID-19 have also been summarized [ 78 , 79 ]. Kotru et al reviewed electrochemical sensing technologies prognostics purposes [ 80 ].…”
Section: Perspectives and Conclusionmentioning
confidence: 99%